Risk of venous thromboembolism and primary prophylaxis in cancer - Pabinger, I.; Ay, C. (Onkologische Welt, 2012)
Venous thromboembolism (VTE) is a common complication in patients with cancer that causes significant morbidity and mortality. Several patient-, tumour- and treatment-related risk factors for VTE in cancer patients have been identified. An effective and safe thromboprophylaxis in cancer patients at high risk of VTE is desirable. Recently, the identification of potential biomarkers and the development of risk scoring models for prediction of cancer-associated VTE have been published. Whether primary VTE prophylaxis based on risk assessment through these biomarkers and risk prediction models might be useful, is currently not yet known. However, thromboprophylaxis is clearly indicated in high-risk situations. While VTE prophylaxis is recommended in cancer patients undergoing surgery and in hospitalised patients with acute disease, studies in ambulatory cancer patients are still rare and evidence for primary VTE prophylaxis is currently limited. In this review, risk factors associated with VTE in cancer patients and current approaches of thromboprophylaxis in different settings, specifically in ambulatory cancer patients are subjected to a critical evaluation.
Keywords: Cancer; venous thromboembolism; thromboprophylaxis